High-CTI (comparative tracking index) high-toughness flame-retardant PET / PC (polyethylene terephthalate / polycarbonate) alloy material and preparation method thereof
By using high-flow ethylene-butyl acrylate copolymer, brominated epoxy resin flame retardant and CZ-G20 flame retardant synergist in PET/PC alloy materials, the surface rubber layer and flame retardant system are formed, and the problems of low CTI grade and insufficient toughness of PET/PC alloy materials are solved, and the high CTI high toughness and flame retardant performance are improved, which is suitable for electrical components.
Patent Information
- Application Number
- CN202510774947.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-11
- Publication Date
- 2025-08-26
AI Technical Summary
During the flame retardant modification process of existing PET/PC alloy materials, there are problems such as low CTI grade and insufficient toughness, especially in high voltage environments, which makes it difficult to reach PLC level 0.
High-flow ethylene-butyl acrylate copolymer is used as toughening agent to form a surface rubber layer to isolate conductive particles, and brominated epoxy resin flame retardant and leakage trace-induced CTI enhancement enhancer CZ-G20 are used as flame retardant synergist. Combined with an appropriate amount of processing aids, high CTI high-toughness flame retardant PET/PC alloy material is prepared through the twin-screw extrusion mechanism.
It significantly improves the CTI level of the material to PLC level 0, enhances the toughness and flame retardant properties of the material, and is suitable for electrical components and meets the safety requirements of high voltage environments.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of PET / PC alloy materials and relates to a high CTI and high toughness flame-retardant PET / PC alloy material and a preparation method thereof. Background Art
[0002] PET (polyethylene terephthalate) is a crystalline thermoplastic with rapid crystallization, chemical resistance, and good melt flowability, but it suffers from low impact strength. PC (polycarbonate), an engineering plastic, offers excellent impact strength but suffers from poor processing fluidity and chemical resistance. Therefore, blending PC and PET, which complement each other's strengths, has significant application value.
[0003] As the electronics and electrical appliance industry continues to develop, the standards for applied materials are becoming increasingly stringent, with PET / PC alloys becoming the primary materials for these applications. For safety reasons, the core components of these applications require flame-retardant materials, making it necessary to modify PET / PC alloys to achieve flame retardancy.
[0004] Existing flame-retardant modification techniques for PET / PC alloys exist in two approaches: halogen-free and halogen-containing. The mainstream approach is to use halogen-containing flame retardants to improve the flame retardancy of PET / PC alloys. However, halogen-containing flame retardants reduce the toughness of PET / PC alloys. Furthermore, halogen-containing flame retardants decompose under high temperatures or electric arcs to produce highly conductive hydrogen halides, which increase the material's conductivity and ultimately reduce its CTI (Comparative Tracking Index).
[0005] In order to improve the toughness of PET / PC alloy materials, the existing technology attempts to add toughening agents to PET / PC alloy materials. For example, patent application publication number CN104693729A discloses a halogen-free flame retardant PC / PET alloy, the components of which are as follows by mass percentage: PC resin 45%-70%, PET resin 5%-30%, halogen-free flame retardant masterbatch 2%-10%, toughening compatibilizer 2%-5%, anti-hydrolysis agent 0.5%-2%, antioxidant 0.1%-0.5%, and other additives 0-1%. Patent application publication number CN104693762A discloses a flame-retardant PC / PET composite material. Its components, by mass percentage, are: 30%-60% PC, 10%-30% PET, 2%-5% compatibilizer, 5%-15% flame retardant, 0.1%-0.5% anti-drip agent, 5%-10% toughening agent, 0.1%-0.5% antioxidant, and 0.5%-1.5% lubricant. While these PC / PET alloys or composites offer improved flame retardancy and toughness, they still contain conductive particles on their surfaces. These particles form a conductive network, generating heat that leads to ignition, resulting in a CTI rating of only PLC 2. This CTI rating remains low, falling short of PLC 0, the highest level for safe use in a 600V voltage environment. The CTI rating still needs to be improved.
[0006] Therefore, there is an urgent need to develop a PET / PC alloy material with high CTI, high toughness and flame retardant properties. Summary of the Invention
[0007] The purpose of the present invention is to solve the above problems existing in the prior art and provide a high CTI and high toughness flame retardant PET / PC alloy material and a preparation method thereof.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0009] A high CTI and high toughness flame-retardant PET / PC alloy material, comprising, by weight, 45-55 parts of PET, 25-35 parts of PC, 4-6 parts of a toughening agent, 13-15 parts of a flame retardant, 2-3 parts of a flame retardant synergist, and 1.7-2.9 parts of a processing aid;
[0010] The melt index of the toughening agent at 190°C and 2.16 kg is 40 g / 10 min, and the toughening agent is ethylene-butyl acrylate copolymer;
[0011] The flame retardant is a brominated epoxy resin flame retardant;
[0012] The flame retardant synergist is the tracking enhancer CZ-G20 (a metasilicate polymer with a special surface treatment, manufactured by Jiangsu Juqian New Material Technology Co., Ltd.);
[0013] The PET / PC alloy material of the present invention has a high CTI. This is due, firstly, to the use of a specific type of toughening agent with high fluidity. During processing, the toughening agent can migrate to the surface of the alloy material to form a rubber layer, isolating the conductive particles and reducing the conductivity of the particles on the alloy surface. Furthermore, the present invention uses flame retardants and flame retardant synergists that have a minimal effect on the material's CTI, thus avoiding a decrease in the insulation properties of the alloy material due to the addition of flame retardants and flame retardant synergists.
[0014] The PET / PC alloy material of the present invention has high toughness because the addition of a toughening agent can increase the impact strength of the material by 8 to 10 times;
[0015] The PET / PC alloy material of the present invention has high flame retardancy, on the one hand because a certain amount of flame retardant and flame retardant synergist is added, and on the other hand because the amount of toughening agent added is moderate, which can avoid the flame retardancy of the alloy material from being reduced due to excessive addition of toughening agent.
[0016] As the preferred technical solution:
[0017] In the high CTI and high toughness flame-retardant PET / PC alloy material described above, the intrinsic viscosity of PET is 0.678±0.010 dL / g, and the low-viscosity PET can effectively encapsulate the flame retardant and the flame retardant synergist.
[0018] In the flame retardant of the high CTI and high toughness flame-retardant PET / PC alloy material described above, the bromine content is 52 wt %. The bromine content is controlled to ensure the effectiveness of the flame retardant and to ensure that the flame retardant performance is qualified.
[0019] The high CTI and high toughness flame-retardant PET / PC alloy material described above comprises, by weight, 1.7 to 2.9 parts of a processing aid, 0.2 to 0.4 parts of an antioxidant (e.g., antioxidant 1010 and antioxidant 168 in a weight ratio of 1:1), 1 to 1.5 parts of a lubricant (e.g., pentaerythritol stearate), and 0.5 to 1 parts of a nucleating agent (e.g., nucleating agent P252).
[0020] A high CTI and high toughness flame retardant PET / PC alloy material as described in any of the above items has a tensile strength of 61.6-64.7 MPa, a flexural strength of 85.4-89.2 MPa, and an impact strength of 8-11.4 kJ / m 2 , flame retardant grade is V0~V2, CTI grade is PLC 0.
[0021] The present invention also provides a method for preparing a high-CTI, high-toughness, flame-retardant PET / PC alloy material as described in any of the above items. The method comprises adding PET, PC, a toughening agent, and a processing aid according to a proportion into a high-speed blender and mixing for 3 to 5 minutes to prepare a mixture A. The flame retardant and a flame retardant synergist are added into the high-speed blender and mixed for 3 to 5 minutes to prepare a mixture B. The mixture A is then added into a twin-screw extruder through a main feed port, and the mixture B is added into the twin-screw extruder through a side feed port. The mixtures are then melted, extruded, and granulated in sequence to obtain the high-CTI, high-toughness, flame-retardant PET / PC alloy material.
[0022] As the preferred technical solution:
[0023] In the method described above, the inner barrel temperature of the twin-screw extruder is 250~270°C, the screw speed is 350~450rpm, the side feeding speed is 10~50Hz, and the vacuum pressure is -0.08~-0.1MPa.
[0024] Beneficial effects:
[0025] (1) The high CTI and high toughness flame-retardant PET / PC alloy material of the present invention uses a high-fluidity ethylene-butyl acrylate copolymer as a toughening agent to form a rubber layer on the surface of the alloy material, thereby reducing the conductive particles on the surface and lowering the surface conductivity. At the same time, through the synergistic effect of the flame retardant synergist and the rubber layer, the decrease in the insulation performance and CTI grade of the alloy material due to the addition of the flame retardant and the flame retardant synergist is avoided, and the CTI grade of the alloy material is finally increased to PLC 0, so that the alloy material can be used as an electrochemical-resistant material in various electrical components.
[0026] (2) The high CTI and high toughness flame-retardant PET / PC alloy material of the present invention is made to have high toughness by adding the above-mentioned toughening agent, thereby effectively improving the impact resistance of the alloy material.
[0027] (3) The high CTI and high toughness flame-retardant PET / PC alloy material of the present invention adopts brominated epoxy flame retardant and special flame retardant synergist as the flame retardant system, which can effectively improve the flame retardant performance of the alloy material and achieve the 0.8mmV0 flame retardant grade of UL 94: 2023 standard. It can be widely used in home appliances, automotive appliances and other fields.
[0028] (4) The preparation method of the present invention has simple steps, is easy to operate, and is suitable for large-scale industrial applications. DETAILED DESCRIPTION
[0029] Below in conjunction with specific embodiment, further set forth the present invention.Should be understood that these embodiments are only used to illustrate the present invention and are not used in limiting the scope of the present invention.In addition, should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall equally within the scope limited by the appended claims of the application.
[0030] The following are the test methods for the relevant performance indicators in each embodiment and comparative example:
[0031] (1) Tensile strength: Tested in accordance with ISO 527-1: 2019 at a speed of 50 mm / min.
[0032] (2) Bending strength: Tested in accordance with ISO 178: 2019 at a speed of 2 mm / min.
[0033] (3) Impact strength: tested in accordance with ISO 180: 2023, with a pendulum energy of 2.75J.
[0034] (4) Flame retardant grade: tested in accordance with UL 94: 2023, thickness 0.8mm.
[0035] (5) CTI level: Tested in accordance with IEC 60112: 2003.
[0036] Example 1
[0037] A method for preparing a high CTI and high toughness flame-retardant PET / PC alloy material, comprising the following steps:
[0038] (1) Raw material preparation;
[0039] PET: 45 parts by weight, intrinsic viscosity 0.678±0.010dL / g;
[0040] PC: 32 parts by weight, manufactured by Covestro Polymers (China) Co., Ltd., brand 2800;
[0041] Toughening agent: 6 parts by weight of ethylene-butyl acrylate copolymer, with a melt index of 40 g / 10 min at 190° C. and 2.16 kg, manufactured by Arkema, France, with the brand name 35BA40T;
[0042] Flame retardant: 14 parts by weight of brominated epoxy resin flame retardant, with a bromine content of 52 wt %; the manufacturer is Suzhou Borida Polymer Materials Co., Ltd., and the brand is CR-225K;
[0043] Flame retardant synergist: 3 parts by weight of tracking enhancer CZ-G20, manufactured by Jiangsu Juqian New Material Technology Co., Ltd.
[0044] Processing aid: 2.2 parts by weight, consisting of 0.3 parts by weight of antioxidant, 1.2 parts by weight of lubricant, and 0.7 parts by weight of nucleating agent;
[0045] Antioxidant: composed of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:1;
[0046] Lubricant: Pentaerythritol stearate;
[0047] Nucleating agent: nucleating agent P252;
[0048] (2) Mixing of raw materials;
[0049] According to the above ratio, PET, PC, toughening agent and processing aid were added into a high-speed blender and mixed for 4 minutes to prepare mixture A;
[0050] Add the flame retardant and flame retardant synergist in the above proportions into a high-speed blender and mix for 4 minutes to prepare a mixture B;
[0051] (3) Preparation of high CTI and high toughness flame retardant PET / PC alloy materials;
[0052] Mixture A was added into the twin-screw extruder through the main feed port, and mixture B was added into the twin-screw extruder through the side feed port. Melting, extrusion, and granulation were performed in sequence. The inner barrel temperature of the twin-screw extruder was 260°C, the screw speed was 400 rpm, the side feed speed was 30 Hz, and the vacuum pressure was -0.08 MPa to obtain a high CTI and high-toughness flame-retardant PET / PC alloy material.
[0053] The final high CTI and high toughness flame retardant PET / PC alloy material has a tensile strength of 61.6MPa, a flexural strength of 85.4MPa, and an impact strength of 11.4kJ / m 2 , flame retardant grade is V0, CTI grade is PLC 0.
[0054] Comparative Example 1
[0055] A method for preparing a PET / PC alloy material is basically the same as that in Example 1, except that the toughening agent is 6 parts by weight of ethylene-methyl acrylate copolymer, manufactured by Dow Chemical Company of the United States, with a brand name AC1125 and a melt index of 0.5 g / 10 min at 190° C. and 2.16 kg.
[0056] The PET / PC alloy material prepared in this comparative example has a tensile strength of 62.8 MPa, a flexural strength of 81.2 MPa, and an impact strength of 11.5 kJ / m2 , flame retardant grade is V0, CTI grade is PLC 2.
[0057] Compared with Example 1, the tensile strength of Comparative Example 1 increased by 1.9%, the flexural strength decreased by 5%, the impact strength increased by 0.9%, the flame retardancy rating remained unchanged, and the CTI rating decreased to PLC 2. This is because Example 1 uses ethylene-butyl acrylate copolymer as a toughening agent, while Comparative Example 1 uses ethylene-methyl acrylate copolymer as a toughening agent. The two toughening agents are of similar types. Therefore, the mechanical properties and flame retardancy ratings of the PET / PC alloy materials obtained in Comparative Example 1 and Example 1 do not change significantly. However, the melt index of the toughening agent in Example 1 is 40g / 10min, while the melt index of the toughening agent in Comparative Example 1 is 0.5g / 10min. The melt index of the toughening agent in Comparative Example 1 is significantly lower. Due to the positive correlation between melt index and fluidity, the fluidity of this toughening agent is also significantly reduced, and the fluidity of the entire alloy material system also deteriorates, making it impossible for the toughening agent to quickly disperse into the surface layer of the entire alloy material system, ultimately resulting in a lower CTI rating. This shows that the melt index of the toughening agent has a significant impact on the CTI rating of the alloy material.
[0058] Comparative Example 2
[0059] A method for preparing a PET / PC alloy material is basically the same as that in Example 1, except that no toughening agent is added.
[0060] The PET / PC alloy material prepared in this comparative example has a tensile strength of 63.4 MPa, a flexural strength of 87.3 MPa, and an impact strength of 5.6 kJ / m 2 , flame retardant grade is V0, CTI grade is PLC 3.
[0061] Compared with Example 1, the tensile strength of Comparative Example 2 increased by 2.9%, the flexural strength increased by 2.2%, the impact strength decreased by 50.8%, the flame retardancy rating remained unchanged, and the CTI rating decreased to PLC 3. The changes in tensile strength, flexural strength, and flame retardancy were not significant. Because Comparative Example 2 lacked a toughening agent, the alloy material lacked toughness, resulting in a significantly lower impact strength than that of Example 1. Since the absence of a toughening agent in Comparative Example 2 prevented the formation of a rubber layer on the alloy surface, thus failing to reduce conductivity, the flame retardant synergist was the only means of increasing the CTI rating. Therefore, the PET / PC alloy material produced in Comparative Example 2 only achieved a maximum CTI rating of PLC 3.
[0062] Comparative Example 3
[0063] A method for preparing a PET / PC alloy material is basically the same as that in Example 1, except that the flame retardant synergist is replaced by an equal weight portion of antimony trioxide.
[0064] The PET / PC alloy material prepared in this comparative example has a tensile strength of 63.2 MPa, a flexural strength of 82.4 MPa, and an impact strength of 12.1 kJ / m 2 , flame retardant grade is V2, CTI grade is PLC 1.
[0065] Compared with Example 1, the tensile strength of Comparative Example 3 increased by 2.6%, the flexural strength decreased by 3.5%, the impact strength increased by 6.1%, the flame retardancy rating decreased to V2, and the CTI rating decreased to PLC 1. The mechanical properties of the PET / PC alloy prepared in Comparative Example 3 did not change significantly. However, due to the reduced effectiveness of antimony trioxide as a flame retardant synergist, the flame retardancy rating of Comparative Example 3 decreased significantly. Furthermore, antimony trioxide more readily forms a conductive layer on the alloy surface, which reduces the alloy's CTI rating during CTI testing, resulting in a maximum CTI rating of only PLC 1.
[0066] Comparing the data from Example 1, Comparative Example 2, and Comparative Example 3, the PET / PC alloy material produced in Example 1, which added a toughening agent and used CZ-G20 as a flame retardant synergist, achieved a higher CTI rating of PLC 0. In contrast, the PET / PC alloy material produced in Comparative Example 2, which lacked a toughening agent, achieved a CTI rating of PLC 3. And in Comparative Example 3, which used antimony trioxide as a flame retardant synergist, achieved a CTI rating of PLC 1. This demonstrates that the toughening agent significantly impacts the alloy material's CTI rating, while CZ-G20, as a flame retardant synergist, has a minimal impact on the alloy material's CTI rating. Furthermore, the toughening agent's impact on the alloy material's CTI rating is far greater than that of CZ-G20.
[0067] Example 2
[0068] A method for preparing a high CTI and high toughness flame-retardant PET / PC alloy material, comprising the following steps:
[0069] (1) Raw material preparation;
[0070] PET: 49 parts by weight, intrinsic viscosity: 0.678±0.010dL / g;
[0071] PC: 27 parts by weight, manufactured by Covestro Polymers (China) Co., Ltd., brand 2800;
[0072] Toughening agent: 5 parts by weight of ethylene-butyl acrylate copolymer, with a melt index of 40 g / 10 min at 190° C. and 2.16 kg, manufactured by Arkema, France, with the brand name 35BA40T;
[0073] Flame retardant: 13 parts by weight of brominated epoxy resin flame retardant, with a bromine content of 52 wt %; the manufacturer is Suzhou Borida Polymer Materials Co., Ltd., and the brand is CR-225K;
[0074] Flame retardant synergist: 2 parts by weight of tracking enhancer CZ-G20, manufactured by Jiangsu Juqian New Material Technology Co., Ltd.
[0075] Processing aid: 1.7 parts by weight, consisting of 0.2 parts by weight of antioxidant, 1 part by weight of lubricant, and 0.5 parts by weight of nucleating agent;
[0076] Antioxidant: composed of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:1;
[0077] Lubricant: Pentaerythritol stearate;
[0078] Nucleating agent: nucleating agent P252;
[0079] (2) Mixing of raw materials;
[0080] According to the above ratio, PET, PC, toughening agent and processing aid were added into a high-speed blender and mixed for 4 minutes to prepare mixture A;
[0081] Add the flame retardant and flame retardant synergist in the above proportions into a high-speed blender and mix for 4 minutes to prepare a mixture B;
[0082] (3) Preparation of high CTI and high toughness flame retardant PET / PC alloy materials;
[0083] Mixture A was added into the twin-screw extruder through the main feed port, and mixture B was added into the twin-screw extruder through the side feed port. Melting, extrusion, and granulation were performed in sequence. The inner barrel temperature of the twin-screw extruder was 260°C, the screw speed was 400 rpm, the side feed speed was 30 Hz, and the vacuum pressure was -0.08 MPa to obtain a high CTI and high-toughness flame-retardant PET / PC alloy material.
[0084] The final high CTI and high toughness flame retardant PET / PC alloy material has a tensile strength of 64.7 MPa, a flexural strength of 87.1 MPa, and an impact strength of 10.3 kJ / m 2 , flame retardant grade is V2, CTI grade is PLC 0.
[0085] Example 3
[0086] A method for preparing a high CTI and high toughness flame-retardant PET / PC alloy material, comprising the following steps:
[0087] (1) Raw material preparation;
[0088] PET: 55 parts by weight, intrinsic viscosity: 0.678±0.010dL / g;
[0089] PC: 25 parts by weight, manufactured by Covestro Polymers (China) Co., Ltd., brand 2800;
[0090] Toughening agent: 4 parts by weight of ethylene-butyl acrylate copolymer, with a melt index of 40 g / 10 min at 190° C. and 2.16 kg, manufactured by Arkema, France, with the brand name 35BA40T;
[0091] Flame retardant: 15 parts by weight of brominated epoxy resin flame retardant, with a bromine content of 52 wt %; the manufacturer is Suzhou Borida Polymer Materials Co., Ltd., and the brand is CR-225K;
[0092] Flame retardant synergist: 3 parts by weight of tracking enhancer CZ-G20, manufactured by Jiangsu Juqian New Material Technology Co., Ltd.
[0093] Processing aid: 2.9 parts by weight, consisting of 0.4 parts by weight of antioxidant, 1.5 parts by weight of lubricant, and 1 part by weight of nucleating agent;
[0094] Antioxidant: composed of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:1;
[0095] Lubricant: Pentaerythritol stearate;
[0096] Nucleating agent: nucleating agent P252;
[0097] (2) Mixing of raw materials;
[0098] According to the above ratio, PET, PC, toughening agent and processing aid were added into a high-speed blender and mixed for 4 minutes to prepare mixture A;
[0099] Add the flame retardant and flame retardant synergist in the above proportions into a high-speed blender and mix for 4 minutes to prepare a mixture B;
[0100] (3) Preparation of high CTI and high toughness flame retardant PET / PC alloy materials;
[0101] Mixture A was added into the twin-screw extruder through the main feed port, and mixture B was added into the twin-screw extruder through the side feed port. Melting, extrusion, and granulation were performed in sequence. The inner barrel temperature of the twin-screw extruder was 260°C, the screw speed was 400 rpm, the side feed speed was 30 Hz, and the vacuum pressure was -0.08 MPa to obtain a high CTI and high-toughness flame-retardant PET / PC alloy material.
[0102] The final high CTI and high toughness flame retardant PET / PC alloy material has a tensile strength of 63.3MPa, a flexural strength of 89.2MPa, and an impact strength of 8kJ / m 2 , flame retardant grade is V0, CTI grade is PLC 0.
Claims
1. A high CTI and high toughness flame retardant PET / PC alloy material, characterized in that: By weight, it is composed of 45-55 parts of PET, 25-35 parts of PC, 4-6 parts of toughening agent, 13-15 parts of flame retardant, 2-3 parts of flame retardant synergist and 1.7-2.9 parts of processing aid; The melt index of the toughening agent at 190°C and 2.16 kg is 40 g / 10 min, and the toughening agent is ethylene-butyl acrylate copolymer; The flame retardant is a brominated epoxy resin flame retardant; The flame retardant synergist is the tracking enhancement agent CZ-G20.
2. The high CTI and high toughness flame retardant PET / PC alloy material according to claim 1, characterized in that: The intrinsic viscosity of PET is 0.678±0.010 dL / g.
3. The high CTI and high toughness flame retardant PET / PC alloy material according to claim 1, characterized in that: The bromine content in the flame retardant is 52wt%.
4. The high CTI and high toughness flame retardant PET / PC alloy material according to claim 1, characterized in that: By weight, 1.7-2.9 parts of processing aids are composed of 0.2-0.4 parts of antioxidants, 1-1.5 parts of lubricants, and 0.5-1 parts of nucleating agents.
5. The high CTI and high toughness flame retardant PET / PC alloy material according to any one of claims 1 to 4, characterized in that: The tensile strength is 61.6~64.7MPa, the flexural strength is 85.4~89.2MPa, and the impact strength is 8~11.4kJ / m 2 , flame retardant grade is V0~V2, CTI grade is PLC 0.
6. A method for preparing a high CTI and high toughness flame-retardant PET / PC alloy material according to any one of claims 1 to 5, characterized in that: According to the ratio, PET, PC, toughening agent and processing aid are prepared into mixture A, and flame retardant and flame retardant synergist are prepared into mixture B. Mixture A is added into a twin-screw extruder through the main feed port, and mixture B is added into the twin-screw extruder through the side feed port. The products are melted, extruded and granulated in sequence to obtain a high CTI and high-toughness flame-retardant PET / PC alloy material.
7. The method according to claim 6, characterized in that The inner barrel temperature of the twin-screw extruder is 250~270℃, the screw speed is 350~450rpm, the side feeding speed is 10~50Hz, and the vacuum pressure is -0.08~-0.1MPa.
Citation Information
Patent Citations
Halogen-free flame-retardant PC / PET alloy
CN104693729A
Flame-retardant PC / PET composite material
CN104693762A
High-GWIT high-CTI thin-wall flame-retardant glass-fiber reinforced low-warpage PET composite material and preparation method thereof
CN108164935A
Flame-retardant polybutylene terephthalate material and preparation method thereof
CN109749375A
Antimony-free flame-retardant modified PC / PET / ABS composition
CN112662156A